Improving Competence and Entrepreneurship through Skills in Using Total Station in Vocational High School - Taufiq Natsir; Anas Arfandi; Dwi Wahyuni Aprianti; Raeny Tenriola Idrus (PT. Global Research Collaboration, 2024)
This study aims to improve students' competence and entrepreneurship through skills training on the use of Total Station at SMKN 5 Majene. Despite adequate school facilities, the curriculum related to surveying technology, especially the use of Total Station, is still underemphasized, even though this tool is standard in modern construction projects. This program conducted training and workshops involving lecturers who are mapping survey experts. In addition, this program also equips students with entrepreneurial knowledge, opens up career opportunities in the surveying and mapping sector, and increases the competitiveness of graduates in the work industry. The methods used include practical training, ongoing coaching, and comprehensive evaluation to ensure objectives are achieved. The results obtained are that the participants (students) of SMKN 5 Majene have the knowledge and skills in operating a Total Station and have entrepreneurial knowledge who are ready to work and able to utilize their technical skills in the world of work in the field of construction and surveying, which is also expected to contribute to the development of the local economy.